A study of the inverse of a free-surface problem. (28th April 2005) - Yahia-Djouadi, R. Ait; Hernane-Boukari, D.; Teniou, D.
Abstract : We prove the existence of an obstacle lying on the bottom of an infinite channel inducing a surface on the upper bound of the fluid domain. This problem is the inverse of the free-surface problem flow which has been studied by several authors. We use the implicit function theorem to establish the existence of the solution of the problem.